Comparison of permanent 125I seeds implants with two different techniques in 500 cases of prostate cancer - Guinot, Jose Luis; Ricós, Jose Vicente; Tortajada, Maria Isabel; Santos, Miguel Angel; Casanova, Juan; Clemente, Jose; Samper, Josefa; Santamaría, Paula; Arribas, Leoncio (Journal of Contemporary Brachytherapy, 2015)
Purpose : To perform a comparative study of 500 consecutive 125 I seeds implants for intracapsular prostate carcinoma with two techniques differing in terms of both strand implantation and planning. Material and methods: From 2002 to 2007 we performed 250 implants with fixed stranded seeds (RapidStrand™) and a preplanning system and from 2007 to 2010, 250 with real-time and ProLink™ system. Mean age was 68 and 66, respectively, median PSA (prostate-specific antigen) 7.3 and 7.2, stage T1-T2a in 98% and 94%, and Gleason ≤ 6 in 96% and 86%. Low risk cases were 81% and 71%. The prescribed dose was 145 Gy to the prostate volume, or 108 Gy plus EBRT 46 Gy in some intermediate risk cases. Hormonal treatment was given to 42% and 28%. Results: Median follow-up was 48 and 47 months, respectively, 14 patients in the first group and 7 patients in the second developed biochemical failure (BF). Actuarial biochemical relapse-free survival (bRFS) at 5 years increased from 90.2% to 97.2% (low risk from 91.3% to 97.2%, intermediate risk from 84.2% to 97.1%). Biochemical failure was independent of hormone treatment. Rectal complications were G1-2 in 1.2% and 5.2%, respectively. A urinary catheter was necessary in 6.9% and 9.6%, and urethral resection in 1.9% and 4.4%. Genitourinary toxicity was G1-2 in 4.6% and 12%, G3-4 in 1.9% and 4.8%. An assessment of mean D90 in a sample of patients showed that the dosimetry in postoperative planning based on CT improved from a mean D90 of 143 Gy to 157 Gy. Conclusions : The outcome of patients with low risk prostate carcinoma treated with 125 I seed is very good with low complications rate. The real-time approach in our hands achieved a more precise seed implantation, better dosimetry, and a statistically non-significant better biochemical control. We have made this our standard technique.